2001
DOI: 10.1111/j.1745-4530.2001.tb00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of WLF and Arrhenius Kinetics to Rheology of Selected Dark‐colored Honey

Abstract: The rheological properties of Common Black Horehound, Globe Thistle, and Squill types of dark‐colored Jordanian honey were examined. The types of honey used were identified via assessing the source of nectar using pollen analysis (Melissopalynology). The apparent viscosity, η, was measured as a function of the shear rate, γ. In addition, the apparent viscosity was measured, at constant shear rate (6.12 s−1), as a function of shearing time. Newton's law of viscosity (i.e., τ=ηγ) was found to adequately (R2∼ 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 10 publications
(6 reference statements)
7
32
1
Order By: Relevance
“…All data sets could be fitted to a single master curve using the WLF model with the fixed Ôuniversal' constants, C 1 ¼ 17:44 and C 2 ¼ 51:6 K (Williams et al, 1955). These results concur with the findings of Al-Malah et al (2001) who also found that the WLF equation, using the Ôuniversal' constants, adequately described the temperature-dependence of viscosity for three honey samples. The Ôuniversal constants' of the WLF equation are actually average values, which have been extracted from data on numerous glass-forming liquids and their use is not successful for all materials.…”
Section: Wlf Modeling Of Viscositysupporting
confidence: 89%
See 2 more Smart Citations
“…All data sets could be fitted to a single master curve using the WLF model with the fixed Ôuniversal' constants, C 1 ¼ 17:44 and C 2 ¼ 51:6 K (Williams et al, 1955). These results concur with the findings of Al-Malah et al (2001) who also found that the WLF equation, using the Ôuniversal' constants, adequately described the temperature-dependence of viscosity for three honey samples. The Ôuniversal constants' of the WLF equation are actually average values, which have been extracted from data on numerous glass-forming liquids and their use is not successful for all materials.…”
Section: Wlf Modeling Of Viscositysupporting
confidence: 89%
“…Although the Arrhenius formalism seems to adequately describe the temperature dependence of honey viscosity, it gives relatively high values for the activation energy, which are more typical of chemical reactions. Similar observations concerning the magnitude of E a derived from viscosity data of three Jordanian honey samples (E a 95.6-97.7 kJ mol À1 , temperature range 20-50°C) have been made in a previous study by Al-Malah et al (2001).…”
Section: Rheological Behavioursupporting
confidence: 74%
See 1 more Smart Citation
“…Although thermal processing is a convenient way to change the consistency of honey and protect it from fermentation (since an increase of water activity during crystallization tends to ferment), high temperature can be detrimental to the quality of honey and its biological properties. Most type of honey show Newtonian behaviour (Bhandari et al 1999;Al-Malah et al 200 1;Zaitoun et al 200 1;Abu-Jdayil et al 2002); however, there are some reports in the literature showing a nonNewtonian behaviour of honey (Munroe 1943;White 1978). Thermal treatment will change the flow behaviour of honey.…”
Section: Introductionmentioning
confidence: 99%
“…The subject has been widely studied and there is extensive literature available on the rheological properties of the honey collected in different parts of the world (Bhandari et al, 1999, Gómez-Díaz et al, 2006, Kayacier & Karaman, 2008Lazaridou et al, 2004;Mossel et al, 2000, Oh & Yoo, 2011Trávníček et al, 2012;Yoo, 2004,). Most of the reports on the subject maintain that honey is a Newtonian fluid whose viscosity depends on temperature and water content (Abu-Jdayil et al, 2002;Al-Malah et al, 2001;Bakier, 2007;Junzheng and Changying, 1998;Sopade et al, 2002;Yanniotis et al, 2006;Zaitoun et al, 2001). Some works indicate that liquid honey may have pseudoplastic properties (Gomez-Diaz et al, 2006;Mehryar et al, 2013) or thixotropic characteristics (White, 1978).…”
Section: Introductionmentioning
confidence: 99%